Alternative manufacturing process of 3-dimensional interconnect device using thermoforming process. (December 2021) - Zulfiqar, S.; Saad, A.A.; Sharif, M.F.M.; Samsudin, Z.; Ali, M.Y.T.; Ani, F.C.; Ahmad, Z.; Abdullah, M.K.
Abstract: In early stages, the electronic circuits have been developed on simple printed circuit boards with multiple copper patterns and components interconnected by lead – free solder. Later on, these are converted to flexible circuits and molded interconnect devices (MID) because of high demand of complex circuit design. Laser machine is used to manufacture 3D MID circuits. An alternative manufacturing process has been introduced in this research. The method is to design functional circuits by using stretchable ink printed on a 2D substrate. Polycarbonate is selected as a substrate on the basis of its glass transition temperature ( T g ). Thermoforming process is then applied to transfer 2D substrate into 3D shape. Reverse engineering technique is used to fabricate the mold through several steps. First, the dimensions of rear lighting is calculated by coordinate measuring machine (CMM), transferred to 3D drawing using SolidWorks. And finally the mold is produced using computer numerical control (CNC) machine. Screen printing technique is opted to print ink on a flat thermoplastic Polycarbonate substrate. The highly conductive circuit will be generated after heating printed ink in oven for about 30 min at 120 °C. The circuit with substrate is further transferred into 3D shape using the thermoforming process. All the light emitted diodes (LEDs) are then fixed on a circuit by dispensing conductive adhesive and cured again in an oven for 10 min at 120 °C, so strong bonds are formed at the joints. The reliability of the circuit is assessed by characterizing mechanical and electrical properties. The designed circuit is then compared with the existing design using scanning electron microscopy (SEM), universal testing, two-point probes multi-meter and spectrometer. The electrical performance of new circuit design shows promising results in terms of power consumption and luminous flux of LEDs and there is no major difference found between them. As a result, the new manufacturing process of printed circuit offers encouraging method in manufacturing the automotive lighting product. Highlights: An alternative method to manufacture and assemble automotive lighting with polymer conductive circuit and adhesive joint Selection of thermoplastic substrate using DSC analysis Printing and curing of conductive ink Transformation of stretchable circuits substrate into 3D rear lighting using thermoforming process